Erosion Potential Of Rainfall In Seberang Perai Area - Mustakim, Norhisham (Universiti Sains Malaysia, 2005)
Soil erosion is highly dependent on rainfall energy which in turn is related to rainfall intensity, rainfall amount, drop size and its distribution. The kinetic energy of rainfall is a major factor initiating soil detachment. The kinetic energy of rainfall and amount of rainfall are highly correlated and the relationship allows a reliable and convenient estimate of the energy load of rainfall from the amount of rainfall. This study attempts to evaluate kinetic energy loads of rainfall and their distribution over the Seberang Perai area in Malaysia. An erosivity map was developed for Seberang Perai area from the daily rainfall of at 8 rainfall stations. This study provided an understanding of the erosive potential of rainfall over Seberang Perai area. The results of the study will contribute in designing conservation works and minimizing erosion risks.